Assessment on defense regime corresponding to systemic resistance induced upon oil palm–ganoderma boninense interaction treated with biological control agents - Md Saad, Muniroh (2021)
Oil palm (Elaeis guineensis) is a significant contributor to Malaysia’s economy, providing both employment and revenue by generating RM 64.9 billion annually in terms of export earnings. However, without positioning efforts in eliminating or controlling major diseases encountered by this commodity crop, sustainability will not be attainable. Thus, it is important to develop early control or preventive measures that will contribute to a sustainable environment that cater the solution to this disastrous disease. Therefore, in this study, effective biological control agents (BCAs) against Ganoderma boninense (UPM13) were studied as a mixture for controlling basal stem rot (BSR) disease infestation in oil palm. The objectives employed to achieve this project were i) To evaluate the antagonistic and compatibility activities of Pseudomonas aeruginosa and Trichoderma asperellum mixture against G. boninense in vitro, ii) To assess the in vivo effects of P. aeruginosa and T. asperellum on the suppression of Ganoderma infestations and as plant growth promoter in oil palm seedlings, and iii) To determine the metabolites and enzymes induced as defense response in treated oil palm seedlings. In this current study, all the BCAs used were subjected to morphological and molecular identification. In addition, these BCAs were also screened for its antagonistic activity against G. boninense via dual culture, culture filtrate test and mycelial growth test. The ability in producing hydrolytic enzymes and plant growth promoting characteristics were also assessed. Both potential BCAs used in this study were identified as T. asperellum and P. aeruginosa. Trichoderma asperellum and P. aeruginosa demonstrated strong antagonistic activity against G. boninense, with percentages of inhibition of radial growth (PIRG) ranging from 69 to 77 percent in dual culture and culture filtrate tests. View under compound microscope with 400× magnifications demonstrated swelled and discontinued hyphae of G. boninense as a result of T. asperellum and P. aeruginosa treatment respectively in mycelium growth test. Observation of G. boninense mycelium in dual culture plate under scanning electron microscope (SEM) exhibited shrink, ruptured and inhibited G. boninense mycelium by P. aeruginosa and T. asperellum. Additionally, the BCAs exhibited growth-promoting characteristics and ability to produce hydrolytic enzymes. Nursery trial was conducted at Ladang 15, Faculty of Agriculture, UPM for 32 weeks on four months old oil palm seedlings (D×P) using dip, place and drench (DPD) inoculation method. Application of BCA treatments demonstrated a significant increase in the vegetative growth of oil palm seedlings compared to the un-treated ones. In terms of vegetative growth, there was no significant difference in plant height, number of fronds, or chlorophyl content when BCAs were applied singly or in a mixture. However, when BCAs were applied in mixture, the bole diameter and root dry weight were considerably greater with ± 3.98 cm and ±41.46 g respectively than when BCAs were applied as single application. Based on the root symptoms, the BCA mixture treatment successfully reduced disease severity (DS) with the lowest DS observed (50%) compared to the positive control with 83.3 percent DS. The BCA treated oil palm seedlings were also tested for plant secondary metabolites induced via gas chromatography-mass spectrometry (GC-MS) analysis and enzyme produced as defense response against G. boninense infection. The treatment with BCAs resulted in the production of plant secondary metabolites which possessed antimicrobial activities and also triggered to the expression of plant defense biochemical regime such as peroxidase (PO), and polyphenol oxidase (PPO) enzymes, total phenolic content (TPC), and lignin content. In conclusion, the BCAs employed in this study demonstrated antagonistic effects against G. boninense in vitro. Mixture application of BCAs resulted in efficient suppression of G. boninense infection in oil palm seedlings via induction of secondary metabolites and enhanced production of plant biochemical defense regime.